Medical jargon and patient comprehension: a linguistic analysis of informed consent practices in Indonesian hospitals - Naridatul Laila (Indonesian Journal of Medical Linguistics, 2026)
Background: Informed consent remains a central ethical requirement in healthcare, yet disparities in health literacy and institutional medical language continue to challenge genuine patient comprehension in Indonesian hospitals. Objective: This study aims to examine how medical jargon, discursive authority, and pragmatic interactional patterns shape patient understanding within written and spoken informed consent practices. Method: Using a qualitative-dominant mixed-method design, this research analyzes 45 consent documents, 26 recorded consultations, and 20 patient interviews through lexical density and readability metrics, Critical Discourse Analysis, and pragmatic repair theory. Results: The findings reveal consistently high lexical density and low readability levels exceeding patients’ educational profiles. Discursive patterns demonstrate systematic de-agentivization and risk transfer framing through passive constructions and legal register. Interactional analysis further shows doctor-dominated turn-taking, frequent closed confirmation checks, and limited patient-initiated repair, correlating with measurable comprehension gaps. Implication: These findings imply that improving informed consent in Indonesian healthcare requires not only simplifying language but also restructuring communicative practices to enhance patient agency, comprehension, and ethical participation. Novelty: The novelty of this study lies in integrating corpus-based computational metrics with critical and pragmatic discourse analysis to conceptualize informed consent as a multi-layered discursive ecosystem rather than a purely legal or ethical instrument.